PEMANFAATAN LIMBAH BOTOL PLASTIK MENJADI PLASTICNET SEBAGAI BAHAN SEPARASI DAN PERKUATAN PADA LAPISAN PERKERASAN JALAN RAYA DI DAERAH TERPENCIL - Dharmawansyah, Dedy; Kurniati, Eti (Jurnal TAMBORA, 2019)
Road infrastructure is one of the important tools in the civil engineering participation in developing the transportation system in Indonesia. It is a central element in the development of the region and the improvement of the economy community. Development of a good road network will have an impact on inter-regional connectivity which is getting easier and it can improve the economy of the people in the region. Nowdays, damage on remote areas had not been optimizing hadling. The Generally soil improvement on the road was using methods such as road packer, Prevabricated Vertical Drain (PVD) or geosynthetic material. But the materials are still relatively expensive to be applied to remote areas which have a bad access road. The research is related to plasticnet aims to obtain alternatives in soil improvement, especially as separators and reinforcement. This research was preceded by did the simulation of tensile strength in plastic material to determine the maximum tensile strength of this material. The next stage is the plastic rope from used bottles that have been cut by using a simple cutting tool, then the net is made with the distance between nets is 5 cm to 20 cm and the overall dimensions produced are about 2 x 3 m. Field testing is carried out by installing a plasticnet on the pavement layer plan on the condition of the layer in dry and wet conditions (saturated with water). Of this condition then it will be able to simulated by giving a vehicle load that is carried out repeatedly. The expected target of this research is to obtain alternative new materials that can be used to separate material and also as pavement layer reinforcement on highway construction that is cheap and efficient, especially for application in remote areas that are difficult to get geosynthetic material.